Remedies, Enforcement and Territoriality - Schwartz, Eric J. (The Columbia Journal of Law & the Arts, 2018)
Thank you to everyone at the Kernochan Center for inviting me to participate and for organizing this symposium. Like Sam Ricketson, I knew and was very fortunate to work with Jack Kernochan, and I am a better copyright lawyer because of him. As with all practicing attorneys, I begin with this caveat: the views I am expressing today are my own and should not be associated with or attributed to any of my clients. What I was asked to speak about on this panel are the challenges confronting authors, producers, and publishers on copyright enforcement, as well as what the treaties require and permit regarding enforcement. I will focus on five key points.